The unity of the Farewell Discourse. The literary integrity of the John 13 - Tolmie, D. F. 1959- (2006)
This book is a revision of Kellum’s doctoral dissertation, completed in 2002 at the Southeastern Baptist Theological Seminary under Dr. Andreas Köstenberger. As the title indicates, the study is devoted to the issue of the unity of John 13:31-16:33, the Farewell Discourse (Kellum prefers the singular ‘Discourse’ instead of the more common ‘Discourses’).
Keywords: Rezension